2022
DOI: 10.1186/s12954-022-00667-9
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in naloxone prescriptions in a University Hospital during the COVID-19 pandemic

Abstract: Background Per the CDC, it is estimated that 69,710 opioid overdose deaths occurred in the United States from September 2019 to September 2020. However, it is unclear whether naloxone prescribing also increased or otherwise fluctuated in this time. The objective of this study was to characterize the naloxone prescribing rate in patients with opioid use disorder (OUD) at the University of Alabama at Birmingham Hospital in 2019 and 2020. Methods A cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Previous studies have found disparities in naloxone prescribing among patients of color [8][9][10][11][12]. Initially, our findings were similar, but after adjusting for confounding variables this difference was no longer statistically significant.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Previous studies have found disparities in naloxone prescribing among patients of color [8][9][10][11][12]. Initially, our findings were similar, but after adjusting for confounding variables this difference was no longer statistically significant.…”
Section: Discussionsupporting
confidence: 72%
“…For those with a current diagnosis of OUD and a presumptive positive UDS for fentanyl the rate was 8.7%. These rates are lower than previous studies [8][9][10][11][12], despite our study including patients that also had a presumptive positive UDS for fentanyl. The rates were also lower despite our study including visits that occurred after the expansion of the CDC's overdose awareness campaign [20] in 2019 and the FDA's recommendation for naloxone that was released in July 2020 [4].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation